THE RELATIONSHIP BETWEEN EAD AND NON-FORMAL LEARNING VIA STREAMING PLATFORMS - Brasil , Freddy Studart de Souza; de Figueiredo, Ana Valéria; Duarte, Ilda Maria Baldanza Nazareth; Magalhães, Edith Maria Marques (Editora Impacto Científico, 2025)
The present article aims to analyze the relationship between Distance Learning (EaD) and learning through streaming platforms, in order to determine whether this type of learning, with all its specific issues, can be considered a form of distance learning akin to traditional EaD. We will provide a brief overview of the history of Distance Education and examine relevant concepts related to learning on streaming platforms, such as virtual community, cyberspace, and cyberculture.DOI: https://doi.org/10.56238/edimpacto2025.092-064